On Being a Five Element Acupuncturist. - Franglen, Nora (Jessica Kingsley Publishers, 2015)
Based on her well-read blog, Nora Franglen provides a rich insight into the inner thoughts and feelings of a master acupuncturist. Covering everything from her love of coffee shops to how to treat patients effectively, it is reveals the truly holistic and rich nature of acupuncture.